POLLINATION ECOLOGY WITH SPECIAL REFERENCE TO INSECTS- A REVIEW - Faheem, Muhammad; Aslam, Muhammad; Razaq, Muhammad (Journal of Research (Science), 2004)
Pollination is the process of transferring pollens to the stigma of conspecific plant and pollination ecology is the mutual relationship between flowers and pollinators. Pollination is a co-evolutionary process between flowering plants and pollinators, which dates back to millions of years. Insects are the most effective pollinators and have important role in pollination ecology. This review deals with different aspects of pollination ecology with special reference to insects. The effect and relationship of different characteristics of flowers, insect pollinators and environmental factors are discussed. Pollinators are greatly influenced by shape, length, colour, odour, nectar, pollen and other rewards of flowers. Effectiveness of pollination also depends upon vision, olfaction, taste, anatomy, food preference, behaviour and learning ability of the pollinators. Physical factors, i. e. altitude, temperature, light, wind and rainfall also influence the flower visiting, foraging behaviour and effectiveness of pollinators.